CHARCOT ARTHROPATHY IN A CONTROLLED DIABETIC PATIENT: A CASE REPORT - Sofiani, Dinda Putri; Decroli, Eva; Aprilia, Dinda; Kam, Alexander; Efendi, Yanne Pradwi; Syahbuddin, Syafril; Silan, Asyumaredha Asril (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Charcot arthropathy is a severe complication of diabetes which is often diagnosed late, characterized by a red, warm, and swollen foot with bone abnormalities on imaging. Most studies report elevated HbA1c as a risk factor in Charcot patients, but there are rare cases with normal HbA1c. If not promptly diagnosed and treated, the condition can lead to deformity, foot ulcers, amputation, and death. CASE A 54-year-old male came to M Djamil General Hospital with complaints of ulcers around the right ankle. The patient has a history of diabetes mellitus (13 years). We found deformity with ulcers and pus in the right ankle joint. We did several examinations to confirm the diagnosis. The laboratory results are random blood glucose 152 mg/dL; fasting blood glucose 65 mg/dL; two-hours postprandial glucose 111 mg/dL; HbA1c 7.0%. CT scan of the lower extremities found osteomyelitis of the tarsal bones with cellulitis; histopatho- logy found chronic and acute inflammation with granulation tissue. The working diagnosis was Charcot arthropathy of the right distal tibia Brodsky Type 3A, and Type 2 Diabetes Mellitus. We performed immobilization, external fixation, sequestrectomy and boot casting and controlled glycemia with medical nutrition therapy and rapid acting insulin for perioperative management. We used antibiotics and analgesics to treat infection and pain. The results were good and the patient was advised to use ankle foot orthosis. CONCLUSION This is a rare case report of Charcot arthropathy in a patient with normal HbA1c. This condition may be associated with rapid HbA1c normalization, which can trigger acute episodes, and the duration of diabetes. Clinicians should assess glycemic history and neuropathic risk factors. Target HbA1c between 7.0 – 8.0% during treatment can facilitate wound healing without increasing mortality.